Oral Pantoprazole for Acid Suppression in the Treatment of Patients with Zollinger-Ellison Syndrome - Barbara Désir; Pierre Poitras (Canadian Journal of Gastroenterology)
BACKGROUND: The management of patients with gastric acid hypersecretion due to gastrinoma, usually recognized as Zollinger-Ellison syndrome (ZES), was radically changed 10 years ago by the use of proton pump inhibitors. Surgical treatment now concentrates on tumour excision, and in the majority of patients, gastrectomy is no longer required to prevent complications of acid hypersecretion that can be managed pharmacologically.